Menilik laut Bali dalam sajak Malam Pengantin di Pesisir Serangan karya Wayan Sunarta - Eirenne Pridari Sinsya Dewi; Putra, Ida Bagus Gede Dharma (Universitas Mulawarman, 2024)
Bali is an island that always attracts tourists with its beauty. This natural beauty makes Bali always succeed as an interesting topic to discuss. Apart from its natural beauty, poetry about Bali is also interesting to research. “Malam Pengantin di Pesisir Serangan” is a poem that explains the condition of Serangan Beach in 1997. This poem, created by Wayan Sunarta, tries to express environmental criticism firmly through the choice of diction. The social criticism in this poem describes two interesting things to study, namely Serangan Beach with its naturalness and Serangan Beach with its modernity. This research uses Riffaterre’s semiotic theory by focusing on the process of interpreting poetry in heuristic and hermeneutic reading. Heuristic reading is the first stage of reading in understanding poetry. At this stage, the poem is read following the rules of the language. After that, hermeneutic reading, namely the process of interpreting poetry using literary conventions.